2016
DOI: 10.1155/2016/3825645
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Serum Affects Quality of Engineered Tissues Produced by the Self-Assembly Approach

Abstract: Despite the emergence of serum-free media for cell culture, the use of serum to supplement the culture media is still essential in order to produce engineered urologic tissues using the self-assembly approach, not only for the stromal compartment but also for the uroepithelium. Effects of sera on thickness of these two compartments were measured and quality of the epithelial differentiation was evaluated. For bladder mucosa substitute reconstruction, the use of postnatal sera failed to produce an adequate uroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, the BF-derived tissues produced using NBCS were weaker ( Figure 6 A and Figure 7 A). Combined with the previously obtained results for the minimal differentiation of urothelial cells on the top of such a stroma [ 24 ], NBCS should be avoided to reconstruct urologic tissues. Such a result could be, in part, explained by the nature of BFs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, the BF-derived tissues produced using NBCS were weaker ( Figure 6 A and Figure 7 A). Combined with the previously obtained results for the minimal differentiation of urothelial cells on the top of such a stroma [ 24 ], NBCS should be avoided to reconstruct urologic tissues. Such a result could be, in part, explained by the nature of BFs.…”
Section: Discussionmentioning
confidence: 92%
“…Adhesion, proliferation, and metabolism of nine fibroblast populations from three different organs were evaluated in 2D cell cultures. Fibroblasts from the skin, bladder, and vagina were chosen because the reconstruction of substitutes of these source organs using the self-assembly method that has been published [ 22 , 24 , 25 , 26 ]. The diversity of primary fibroblast populations in terms of organ type, anatomical sites, sex, and age constitutes one of the limitations of this article.…”
Section: Discussionmentioning
confidence: 99%
“…4 Our results showed that the source of serum influenced the production of ECM by cells in long-term cultures in a clearly species-dependent manner. Similarly, Chabaud et al 30 looked at the influence of eight different serum sources on the ECM production by human and rabbit dermal fibroblasts cultured for 4 weeks. Both species showed high serum-source dependency when final tissue thickness was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, our group reported that a self-assembled human skin model, composed of healthy fibroblasts and keratinocytes, could produce a well-differentiated epidermis independently of the presence or absence of serum during the culture process [29] . These results suggest that using calf serum at an early state during the production of the substitutes is suitable to allow cell growth while using serum-deprived medium at an advanced state is acceptable to reduce unforeseen interactions and to avoid individual differences between serum lots [30] .…”
Section: Introductionmentioning
confidence: 90%